Improved Topic Modeling in Biomedical Texts Using UMLS: A MedMentions Approach - Jayabharathi, S.; Logambal, M. (Journal of Neonatal Surgery, 2025)
Effectively extracting and classifying topics from large volumes of medical texts is crucial for knowledge discovery and information retrieval in biomedical research. Traditional topic modeling techniques, while useful, often struggle to capture the intricate semantics of medical terminology. This research investigates how integrating Unified Medical Language System (UMLS) principles can enhance topic modeling using the MedMentions dataset. We evaluate four approaches: BERTopic, Latent Dirichlet Allocation (LDA), LDA with a Recurrent Network (LDA-RNet), and a novel BERTopic with a Recurrent Network (BERTopic-RNet). Our goal is to improve topic coherence and relevance by incorporating UMLS concepts into these models. Experimental results demonstrate that UMLS-enhanced models significantly outperform conventional methods in both topic coherence and clinical relevance. This study provides valuable insights into the application of advanced topic modeling techniques in medical text analysis, paving the way for more effective and interpretable medical data mining.